2011
DOI: 10.2967/jnumed.110.084954
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Perfusion Reserve After a PET-Driven Revascularization Procedure: A Strong Prognostic Factor

Abstract: Not all patients treated on the basis of PET-proven viability benefit from revascularization. Myocardial perfusion reserve (MPR) predicts survival in patients not undergoing revascularization. In the present study, we investigated whether MPR is related to survival in ischemic heart disease (IHD) patients after a PET-driven intervention. Methods: Between 1995 and 2003, 119 consecutive patients with chronic IHD underwent a PETdriven revascularization procedure based on ischemia-viability assessment with PET. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…Slart et al reported that patients with low MFR (,1.34) had the poorest outcomes compared with the 2 other groups (MFR . 1.69 and 1.34-1.69) (25). Similarly, the results from this study showed that patients with low MBR-IR have poorer prognoses than patients with high MBR-IR.…”
Section: Prognostic Value Of Mbr-ir For Macesupporting
confidence: 75%
“…Slart et al reported that patients with low MFR (,1.34) had the poorest outcomes compared with the 2 other groups (MFR . 1.69 and 1.34-1.69) (25). Similarly, the results from this study showed that patients with low MBR-IR have poorer prognoses than patients with high MBR-IR.…”
Section: Prognostic Value Of Mbr-ir For Macesupporting
confidence: 75%
“…Therefore, the influence of specific regional measures cannot be evaluated from this study alone. Finally, our population showed a discrete prevalence of DM2 patients, which might not concur with DM2 prevalence in patients referred to cardiac PET imaging; nevertheless, it portraits the prevalence in the general population as well as in previous published reports 13,14,18…”
Section: Limitationscontrasting
confidence: 68%
“…46,49,50,53,[92][93][94] Consistently, patients with more severely reduced stress MBF and MFR are at higher risk than patients with preserved values or modest reductions. An analysis of the relationship between MFR and cardiac mortality suggests an excellent prognosis for an MFR of more than 2 and a steady increase in cardiac mortality for an MFR of less than 2 ( Figure 8).…”
Section: Prognostic Assessmentmentioning
confidence: 91%